An evaluation of the pragmatics in the "Cutting Edge" intermediate textbooks - Farashaiyan, Atieh; Tan, Kim Hua; Shahragard, Rahman (Penerbit Universiti Kebangsaan Malaysia, 2018)
Regardless of the prodigious impacts of today’s technologies and the substantial influence of language learning through the mediation of computers the world over, coursebooks undeniably have an important role in ESL settings. Accordingly, regular evaluation of textbooks’ materials is a vital task for experts in the field. The evaluation not only can contribute to the learning and teaching process, it also warrants its suitability for the contextual and individual usage. Evaluation is regarded as an inherent section of the teaching and learning procedures. As such, the current study intends to evaluate the pragmatic content of Cutting-Edge intermediate text books (Sarah & Peter 2007), which are currently used in most ESL language colleges. Specifically, it analyzes the conversation sections of all Cutting-Edge intermediate books based on the two pragmatic variables: language functions and speech acts. , The study also investigates the provision of sufficient data with regard to context and meta-pragmatics included in these textbooks. The pragmatic taxonomies, Halliday’s (1978) and Searle’s (1976) models were employed in data analysis. The findings illustrated that pragmatic materials were not sufficient to develop learners’ second language pragmatic features. Furthermore, the conversation parts were not efficient and functional from the pragmatic point of view.